Manchester Protocol at a school hospital emergency service - Mayara Raphaela Morais Rezende; Flavia Falci Ercole; Selme Silqueira de Matos; Miguir Terezinha Vieccelli Donoso (Rev Rene)
Objective: to analyze the flow of directing patients triaged by the Manchester Protocol in the emergency service of a school hospital. Methods: a retrospective, descriptive and documentary study using triage records. The sample was composed of 364 records that were analyzed through descriptive statistics, using simple and relative frequencies and measures of central tendency. Results: the most frequent complaints were those related to the musculoskeletal system (26.1%) and gastrointestinal system (15.1%). The highest demand was for general practice (47.5%). The most frequent risk classification was green (78.3%). Most of the individuals studied received hospital discharge (92.6%). Conclusion: the results suggest that urgency and emergency units are being sought to solve problems that could be solved by primary care units.